The Problems Implementing Academic Supervision in Pandemic and New Normal Period in Senior High School - Febi Eldami Menda; Yari Dwikurnaningsih (Mimbar Ilmu, 2023)
Implementing academic supervision in schools has yet to be carried out optimally. Supervisors still need to follow up on the results of supervision. This research aims to analyze the problem of implementing academic supervision during the pandemic and the new normal. This type of research is qualitative. The research subjects were school principals and teachers. Data was collected through interviews, open questionnaires, FGDs, and documentation studies. The data analysis technique uses descriptive qualitative analysis. The results of this study indicate that during the pandemic academic supervision activities could not be carried out due to the problem of unsupported internet access, teachers' ability to operate IT was still low, especially teachers who were age adrift and school principals did not know for sure the mechanisms for implementing online supervision. In the new normal period, the problem with this academic supervision activity was that the preliminary meeting stage was sometimes not carried out, so teachers were usually given a sudden schedule of supervision activities, academic supervision activities had not used a variety of approaches and methods, and follow-up supervision had not been carried out. It was concluded that during the pandemic and new normal, the implementation of supervision still experienced problems that needed to be of concern to the school principal so that in the future, the implementation of supervision could be carried out more optimally.